1997
DOI: 10.1016/s0920-5632(97)00187-4
|View full text |Cite
|
Sign up to set email alerts
|

J/ψ production at the LHC

Abstract: We firstly examine hadroproduction of prompt J/ψ's at the Fermilab Tevatron in a Monte Carlo framework by means of the event generator PYTHIA 5.7 in which those colour-octet processes relevant for charmonium production have been implemented accordingly. We find that colour-octet matrix elements presented in literature from pp collider data are systematically overestimated due to overlooking of the effective primordial transverse momentum of partons (i.e. including higher-order QCD effects). We estimate the siz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…On the other hand, once implemented Altarelli-Parisi evolution in our framework, the new extracted values of the color-octet ME < O 8 ( 3 S 1 ) > increase (table 1), recovering a similar result as in previous extractions [9]. On the other hand, the numerical values obtained for M 3 even decrease slightly, reinforcing the conclusions reported in our former work [1][2][3][4].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…On the other hand, once implemented Altarelli-Parisi evolution in our framework, the new extracted values of the color-octet ME < O 8 ( 3 S 1 ) > increase (table 1), recovering a similar result as in previous extractions [9]. On the other hand, the numerical values obtained for M 3 even decrease slightly, reinforcing the conclusions reported in our former work [1][2][3][4].…”
Section: Discussionsupporting
confidence: 87%
“…Nevertheless, in order to assess the significance of the cut-off on the values of the long-distance parameters we performed new fits to Tevatron data by changing p min t . We found that, by varying p min t in the [1,2] GeV range, the 3 S (8) 1 ME showed almost no appreciable change, whereas the 1 S…”
Section: Cut-offmentioning
confidence: 81%
See 2 more Smart Citations
“…In a series of previous papers [2,3,4,5] we examined charmonium hadroproduction in a Monte Carlo framework, using PYTHIA 5.7 [6] event generator with the colour-octet model (COM) [7] implemented in. Basically, such a production mechanism is based on the formation of an intermediate coloured state during the hard partonic interaction, evolving non-perturbatively into physical heavy resonances in the final state with certain probabilities governed by NRQCD [8].…”
Section: Introductionmentioning
confidence: 99%